2021
DOI: 10.3390/metabo11090643
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Metabolomics: Strategies to Assess Time-Dependent Postmortem Changes of Diazepam, Nordiazepam, Morphine, Codeine, Mirtazapine and Citalopram

Abstract: Postmortem redistribution (PMR) can result in artificial drug concentration changes following death and complicate forensic case interpretation. Currently, no accurate methods for PMR prediction exist. Hence, alternative strategies were developed investigating the time-dependent postmortem behavior of diazepam, nordiazepam, morphine, codeine, mirtazapine and citalopram. For 477 authentic postmortem cases, femoral blood samples were collected at two postmortem time-points. All samples were quantified for drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In inhibitory synapses, the Gephyrin is one of the most studied proteins, belongs to the core scaffolding proteins, and plays an important role in synaptic anchoring with GABAR subtypes ( Hoffmann and Milovanovic, 2021 ). Gephyrin participates in the anchoring of GABAARs in the postsynaptic region, affects the aggregation and diffusion of synaptic GABAARs, regulates the number of gephyrins, and regulates inhibitory synaptic plasticity ( Bai et al, 2021 ; Brockbals et al, 2021 ; Hoffmann and Milovanovic, 2021 ). Gephyrin and GABAA are interdependent, studies have shown that knocking out gephyrin will destroy GABAAR clusters without affecting their overall protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In inhibitory synapses, the Gephyrin is one of the most studied proteins, belongs to the core scaffolding proteins, and plays an important role in synaptic anchoring with GABAR subtypes ( Hoffmann and Milovanovic, 2021 ). Gephyrin participates in the anchoring of GABAARs in the postsynaptic region, affects the aggregation and diffusion of synaptic GABAARs, regulates the number of gephyrins, and regulates inhibitory synaptic plasticity ( Bai et al, 2021 ; Brockbals et al, 2021 ; Hoffmann and Milovanovic, 2021 ). Gephyrin and GABAA are interdependent, studies have shown that knocking out gephyrin will destroy GABAAR clusters without affecting their overall protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diazepam can be abused for entertainment or in other situations. Determination of diazepam levels in whole blood, serum, plasma, oral samples hair, and urine by UPLC-MS/MS is helpful to study of the pharmacokinetics of diazepam and has forensic significance ( Laloup et al, 2007 ; Wang et al, 2017 ; Brockbals et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variable changes from the admission blood to that taken later has also been seen in a number of time series studies from the Zurich Institute of Forensic Medicine for morphine and number of other opioids, anti‐depressants, anti‐psychotics, and benzodiazepines. On average most drugs showed only small net increases (Brockbals et al, 2018; Brockbals, Staeheli, et al, 2021; Brockbals, Wartmann, et al, 2021; Staeheli et al, 2017).…”
Section: Time‐dependent Redistributionmentioning
confidence: 97%
“…It is now widely acknowledged that, although peripheral blood is less prone to postmortem changes in drug concentrations, these changes in fact occur [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%